Maternal conceptions in classical literature and philosophy - Sharrock, Alison; Keith, Alison (Phoenix. Supplementary volume ;, 2020)
"Unlike many studies of the family in the ancient world, this volume presents readings of mothers in classical literature, including philosophical and epigraphic writing as well as poetic texts. Rather than relying on a male viewpoint, the essays offer a female perspective on the lifecycle of motherhood. Although almost all ancient authors are men, this book nevertheless aims to unpack carefully the role of the mother--not as projected by the son or other male relations, but from a woman's own experiences--in order to better understand how they perceived themselves and their families. Because the primary interest is in the mothers themselves, rather than the authors of the texts in which they appear, the work is organized according to the lifecycle of motherhood instead of the traditional structure of the chronology of male authors. The chronology of the male authors ranges from classical Greece to late antiquity, while the motherly lifecycle ranges from pre-conception to the commemoration of offspring who have died before their mothers."--